Ethnobotanical and phytochemical investigation of Randia echinocarpa (Rubiaceae) - BYE, ROBERT; MATA, RACHEL; LINARES, EDELMIRA; ALBOR, CARLOS; CASTAÑEDA, PERLA C.; DELGADO, GUILLERMO (Anales del Instituto de Biología serie Botánica, 2009)
THE FRUITS OF "GRANJEL", RANDIA ECHINOCARPA , ARE COMMONLY EMPLOYED UN THE TREATMENT OF FIDNEY ALIMENTS IN MEXICO, THE ECHINATE FRUITS ARE PROBABLY A RECENT INTRODUCTION TO THE MEXICAN NATIONAL ""HERBOLARIA"" AND THEIR USE MOST LIKELY ORIGINATED IN CENTRAL MEXICO. MANNITOL STOSTEROL, QUINOVIC, OXOQUINOVIC, URSOLIC AND OLEANOLIC ACIDS WERE EXTRACTED FROM FRUITS AND IDENTIFIED. THE TRITERPENOID CONTENT OF THIS SPECIES IS CONSISTENT WITH THE CHEMICAL PROFILE OF THE GENUS RANDIA AND RELATED GENERA, EVEN THOUGH MANNITOL IS AN OSMOTIC DIURETIC, ITS PRESENCE DOES NOT EXPLAIN TH THERAPEUTIC PROPOERTIES ATTRIBUTED TO "GRANJEL" IN MEXICAN POPULAR MEDICINE.